512 ACADEMIC RESEARCH CONSORTIUM HIGH BLEEDING RISK CRITERIA ASSOCIATED WITH ONE-YEAR NACES IN A MULTICENTER COHORT OF OLDEST OLD STEMI PATIENTS. (15th December 2022) - Ruzzarin, Alessandro; Zilio, Filippo; Muraglia, Simone; Unterhuber, Matthias; Baessato, Francesca; Bonmassari, Roberto; Flaim, Massimo; Zanon, Sofia; Oberhollenzer, Rainer; Donazzan, Luca
Abstract: Introduction: The balance between thrombotic and bleeding events after myocardial revascularization is of paramount importance. Patients with higher bleeding risk are at high risk for complications. Age and frailty are also major risk factors for complications. We sought to evaluate the incidence of major bleeding events (BE) and their impact on prognosis in a real life oldest old (i.e. >85 years) ST elevation myocardial infarction (STEMI) patients population. Methods: We evaluated all consecutive oldest old STEMI patients hospitalized in two hub-centers between January 2010 and June 2021. Patients were stratified according to Academic Research Consortium for High Bleeding Risk (ARC-HBR) in high bleeding risk (HR) and non-HR (nHR) patients. BE were defined according to the Bleeding Academic Research Consortium (BARC) criteria, BARC 3 or 5. Patients were also divided in groups according to anti-thrombotic therapy (AT) regimens at discharge: single antiplatelet therapy (SAPT), dual antiplatelet therapy (DAPT) or triple therapy (DAPT plus oral anticoagulation) (TT). Net adverse clinical event (NACE) was defined as a composite of all-cause mortality, myocardial infarction, stroke, or major bleeding. Follow-up data were determined from local clinical records during a twelve-months period. Results: 340 oldest old (mean age 88.6 ± 2.9 years, 52.6% female) STEMI patients were eligible for the analysis. 161 patients (47.4%) were categorized as nHR and 179 patients (52.6%) as HR. AT regimens at discharge were: 28 patients with SAPT (8.2%), 276 with DAPT (81.2%) and 36 with TT (10.6%). The overall incidence of BE was 4.6% within 12 months, without difference between nHR and HR patients (3.0% vs 5.9%, p=0.16). No BE were found in the SAPT group while the incidence of BE in the HR group was not statistically different between the DAPT and TT regimens (11.2% vs 9.5%; p=0.8). The incidence of NACE was statistically higher in HR than nHR patients (40.9% vs 25.5%, p<0.01) at 1-year. In addition, time-to-NACE was statistically inferior in HR group than nHR group (256.2 days vs 294.2 days, p<0.01) (Figure). Conclusions: Our oldest old STEMI population was characterized by a large proportion of HR patients according to ARC-HBR criteria. This population experienced a higher rate of NACE in a shorter time when compared to nHR patients in the same age group.